Genetic Dissection of Tissue-Specific Apolipoprotein E Function for Hypercholesterolemia and Diet-Induced Obesity. - Tobias Wagner; Alexander Bartelt; Christian Schlein; Joerg Heeren (PLoS ONE)
ApoE deficiency in mice (Apoe-/-) results in severe hypercholesterolemia and atherosclerosis. In diet-induced obesity, Apoe-/- display steatohepatitis but reduced accumulation of triacylglycerides and enhanced insulin sensitivity in white adipose tissue (WAT). Although the vast majority of apoE is expressed by hepatocytes apoE is also abundantly expressed in WAT. As liver and adipose tissue play important roles for metabolism, this study aims to outline functions of both hepatocyte- and adipocyte-derived apoE separately by investigating a novel mouse model of tissue-specific apoE deficiency. Therefore we generated transgenic mice carrying homozygous floxed Apoe alleles. Mice lacking apoE either in hepatocytes (ApoeΔHep) or in adipose tissue (ApoeΔAT) were fed experimental diets. ApoeΔHep exhibited slightly higher body weights, adiposity and liver weights on diabetogenic high fat diet (HFD). Accordingly, hepatic steatosis and markers of inflammation were more pronounced compared to controls. Hypercholesterolemia evoked by lipoprotein remnant accumulation was present in ApoeΔHep mice fed a Western type diet (WTD). Lipidation of VLDL particles and tissue uptake of VLDL were disturbed in ApoeΔHep while the plasma clearance rate remained unaltered. ApoeΔAT did not display any detectable phenotype, neither on HFD nor on WTD. In conclusion, our novel conditional apoE deletion model has proven here the role of hepatocyte apoE for VLDL production and diet-induced dyslipidemia. Specific deletion of apoE in adipocytes cannot reproduce the adipose phenotype of global Apoe-/- mice, suggesting that apoE produced in other cell types than hepatocytes or adipocytes explains the lean and insulin-sensitive phenotype described for Apoe-/- mice.